Biologische Veränderungen im Versenkungsgebiet für schwach radioaktive Abfälle im Iberischen Tiefseebecken? - Vobach, Michael; Kellermann, Hans-Jürgen (2001)
From 1979 to 2000, the site for the dumping of low-level radioactive wastes and an unaffected site in the North-east Atlantic were investigated to determine the biomass data of the benthopelagic nekton and the benthic organisms. The investigation shall demonstrate the influence on the biocoenosis of the so-called "artificial reef effect", caused by dumped waste drums. For sampling benthopelagic and benthic organisms, we used a modified Agassiz trawl, called the Deep-sea Closing Net. With the exception of the “Amperima event” in 1996 – a unique occurrence of a large number of sea-cucumbers – there was no change in the composition of benthopelagic and benthic organisms through the years. The biomass of the benthopelagic nekton was characterized by Macrouridae(rat-tailed fishes) and the main tax on of the benthos was Actiniaria (sea-anemones).